Mineral Reserves in Castor Beans: The Dry Seed - Lott, John N. A. (1982)
Elemental composition and distribution of the mineral reserves in the endosperm and embryo tissues of Ricinus communis cultivars Hale and Zanzibarensis were investigated. Energy dispersive x-ray analysis was used to determine the elemental composition of the globoid crystals, while atomic absorption spectrometry allowed quantification of the elements, particularly Ca, in various seed regions. No major differences were found between the two cultivars with regard to the elemental distribution in globoid crystals. While the majority of globoid crystals contained P, K, and Mg, the occasional one also contained Ca. In extremely rare instances, Fe was detected in globoid crystals. Ca-containing globoid crystals were more common in provascular cell protein bodies in the stem and radicle. Polarized light microscopy, micro-incineration, and acid solubility tests demonstrated the presence of calcium oxalate crystals in the innermost testa which adheres to the endosperm and is often mistakenly identified as endosperm. Atomic absorption spectrometry revealed that most of the calcium present in castor bean seeds is localized in the testa. On a perseed-region basis, the much larger endosperm contains more Ca than does the embryo. However, on a unit-weight basis, the radicle-plus-stem regions contain considerably more Ca than does the cotyledon or endosperm, an observation that is consistent with the observed distribution pattern for Ca-containing globoid crystals.